Materials - Morgan, Sally; Morgan, Adrian (New York : Facts on File, 1994)
Examines the links between design in the natural world and design in modern technology through an investigation of the basic principles of materials, and includes simple experiments, definitions of key terms, photographs, and diagrams.
Atoms and elements -- States of matter -- Polymers -- Building materials -- Calcium-rich materials -- Rubber and glue.
Includes index.
Booklist.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Junior High School.
6.9
4-6
Keywords: Materials -- Juvenile literature; Materials; Matter; Materials; Matter